2017
DOI: 10.5121/ijcnc.2017.9107
|View full text |Cite
|
Sign up to set email alerts
|

RFID Localisation for Internet of Things Smart Homes : A Survey

Abstract: The Internet of Things (IoT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Henceforth, current techniques are insufficient to support trust establishment in the IoT . In IoT healthcare applications, for example, the information would be supplied by a range of heterogeneous devices.…”
Section: Related Workmentioning
confidence: 99%
“…Henceforth, current techniques are insufficient to support trust establishment in the IoT . In IoT healthcare applications, for example, the information would be supplied by a range of heterogeneous devices.…”
Section: Related Workmentioning
confidence: 99%
“…Many localization algorithms have been designed for wireless sensor networks for both indoor and outdoor environments [24]. For example, Alsinglawi et al [15] have identified Radio Frequency Identification (RFID) technologies as a key enabler technology for the IoT due to its cost-effectiveness, high readability rates, automatic identification and energy efficiency characteristics. However, one of the major limitations of RFID technologies is that it needs to equip the environment with a set of pre-identified markers and thus limits the openness of the system.…”
Section: B Localization In the Iotmentioning
confidence: 99%
“…Compared to the conventional backscatter communication scheme in radio frequency identification (RFID) systems, AB communication does not require a dedicated energy-emitting reader, and relies solely on external energy sources in the ambient environment, such as WiFi, public radio, and cellular transmit power. As such, the application of AB communication can effectively reduce the deployment cost of large-size IoT network, such as smart homes, smart cities, and environment monitoring [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the conventional backscatter communication scheme in radio frequency identification (RFID) systems, AB communication does not require a dedicated energy-emitting reader, and relies solely on external energy sources in the ambient environment, such as WiFi, public radio, and cellular transmit power. As such, the application of AB communication can effectively reduce the deployment cost of large-size IoT network, such as smart homes, smart cities, and environment monitoring [3], [4], [5].There has been tremendous research interests recently on ambient backscatter communications [6], [7]. For instance, [8] analyzed the bit error rate of an AB communication link when the receiver uses an energy detector to detect the 1bit information transmitted per channel use.…”
mentioning
confidence: 99%